Impact of cowl deflections on scramjet intake aerodynamics with shock-on-lip condition - Muhammad Yuhendri, Yoga Farhans; Nik Mohd, Nik Ahmad Ridhwan; Mat, Shabudin; Mohd Nasir, Mohd Nazri; Othman, Norazila; Mohd Rafie, Azmin Shakrine; Azami, Muhammad Hanafi (Aeronautical and Astronautical Society of the Republic of China, 2023)
The design of the Scramjet intake has a greater effect on the overall performance of the engine than any other component. By adjusting the leading edge's sharpness, length, and deflection, air compression can be maximized. To enhance overall pressure recovery, a shock-on-lip condition is frequently applied to a standard supersonic inlet. The design of a two-ramp mixed compression intake for freestream Mach numbers 5.5 to 7 is examined in this paper, taking into account the shock-on-lip condition in all analyses. Using inviscid numerical models, the effects of the various deflections of the cowl are investigated. Due to the shock-on-lip effect, the captured mass flow rate decreases linearly as the isolator area and height decrease with increasing Mach number. As the Mach number increases, stronger shocks result in higher pressure and temperature ratios. Additionally, the total pressure recovery, which decreases with increasing Mach number, is positively influenced by the angle at which the cowl is deflected. Due to the significant increase in isolator height brought on by the low Mach number shockwave crossing point, shock-on-lip was still present and the results for Mach 5.5 were less than ideal.